2010
DOI: 10.1038/cddis.2010.69
|View full text |Cite
|
Sign up to set email alerts
|

The CD14+/lowCD16+ monocyte subset is more susceptible to spontaneous and oxidant-induced apoptosis than the CD14+CD16− subset

Abstract: Human monocytes can be classified into two subsets with distinctive characteristics. In this study, we report a difference in apoptotic potential between these two subsets with CD14+/lowCD16+ monocytes being more susceptible than CD14+CD16− monocytes to undergo spontaneous apoptosis and apoptosis induced by reactive oxygen species (ROS). By global transcriptomic and proteomic approaches, we observed that CD14+/lowCD16+ monocytes expressed higher levels of pro-apoptotic genes and proteins such as TNFα, caspase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 41 publications
6
49
1
1
Order By: Relevance
“…These show that the nonclassical subset is the most mature subset, as cell-cycle withdrawal is normally associated with highly differentiated cells. 28 The results of this analysis were consistent with previous studies, which show that the CD16 ϩ monocytes were proapoptotic 29 and that CD16 ϩ monocytes are more mature. 19,30 The 3 monocytes subsets are defined by different transcriptional profiles…”
Section: Three Human Monocyte Subsets E19supporting
confidence: 82%
“…These show that the nonclassical subset is the most mature subset, as cell-cycle withdrawal is normally associated with highly differentiated cells. 28 The results of this analysis were consistent with previous studies, which show that the CD16 ϩ monocytes were proapoptotic 29 and that CD16 ϩ monocytes are more mature. 19,30 The 3 monocytes subsets are defined by different transcriptional profiles…”
Section: Three Human Monocyte Subsets E19supporting
confidence: 82%
“…Our findings are in line with a previous publication demonstrating an increased mitochondrial activity in CD16 1 monocytes (including nonclassical and intermediate monocytes). 50 The same study also noted a higher susceptibility toward apoptosis induced by reactive oxygen species, which correlated with lower expression of glutathione (GSH)-metabolizing genes such as GSH peroxidase (GSP1) and microsomal GSH S-transferase (MGST1), 50 2 oxidative damagelimiting genes that also show weaker CAGE signals in nonclassical monocytes in the present study.…”
Section: Discussionmentioning
confidence: 51%
“…Our previous work showed that a complex network of survival and apoptotic factors controls the dynamic behaviour of monocyte lifespan . Furthermore, timely activation of apoptosis in monocytes is controlled by negative and positive regulators . We found that caspase‐3, a member of the conserved cysteine‐aspartate‐specific proteases, is essential for monocyte apoptosis .…”
Section: Introductionmentioning
confidence: 82%
“…Yet, our understanding of the monocyte function and lifespan is mainly based on the knowledge of CD16 − monocytes. Differences in oxidant‐induced apoptosis and glucocorticoid‐induced apoptosis in CD16 + and CD16 − subsets have been recently reported . The increased expression of glucocorticoid receptors on CD16 + may suggest subset‐specific mechanisms involved in the regulation of monocyte numbers.…”
Section: Introductionmentioning
confidence: 94%